The Timeless African and the Versatile Indian in Seventeenth-Century Travelogues - Duquet, Michel (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2003)
AbstractThe seventeenth century saw the early stages of significant trading on the west coast of Africa as well as the establishment of permanent settlements in North America by Dutch, French and English explorers, merchants, colonists and missionaries in a period marked by the imperial contest that had been set in motion on the heels of the discovery of America in 1492. The travelers who wrote about their voyages overseas described at length the natives they encountered on the two continents. The images of the North American Indian and of the African that emerged from these travel accounts were essentially the same whether they be of Dutch, French or English origin. The main characteristic in the descriptions of African native populations was its permanent condemnation while representations of the Indian were imbued with sentiments ranging from compassion, censure and admiration. The root causes for this dichotomy were the inhospitable and deadly (to Europeans) tropical environment of Africa’s West Coast and the growing knowledge of local societies that Europeans acquired in North America. The analysis of the contrasting images of natives on both sides of the Atlantic and the context within which they were produced are the focus of the paper.